Jak Stat signaling and cancer: Opportunities, benefits and side effects of targeted inhibition - Groner, Bernd; von Manstein, Viktoria (Molecular and cellular endocrinology, 2017)
The effects of Jak Stat signaling and the persistent activation of Stat3 and Stat5 on tumor cell survival, proliferation and invasion have made the Jak Stat pathway a favorite target for drug development and cancer therapy. This notion was strengthened when additional biological functions of Stat signaling in cancer and their roles in the regulation of cytokine dependent inflammation and immunity in the tumor microenvironment were discovered. Stats act not only as transcriptional inducers, but affect gene expression via epigenetic modifications, induce epithelial mesenchymal transition, generate a pro-tumorigenic microenvironment, promote cancer stem cell self-renewal and differentiation, and help to establish the pre-metastatic niche formation. The effects of Jak Stat inhibition on the suppression of pro-inflammatory responses appears most promising and could become a strategy in the prevention of tumor progression. The direct and mediated mechanisms of Jak Stat signaling in and on tumors cells, the interactions with other signaling pathways and transcription factors and the targeting of the functionally crucial secondary modifications of Stat molecules suggest novel approaches to the future development of Jak Stat based cancer therapeutics.